Decision-making determinants in working women's clothes purchasing - Malaysia evidence - Nezakati, Hossein; Chin, Sock Khim; Asgari, Omid (International Association of Computer Science and Information Technology, 2011)
Nowadays so many researches about the decision-making models of consumer behavior are done,however these kinds of researches does not specify determinants of decision-making in the purchased of consumers. Since consumer’s attitude may reduce their purchase or increase it,consideration of determinants of decision-making process in purchase goods would be justified. This Study aimed to examine the determinants of decision-making on the purchased of working women’s clothing in Malaysia. Therefore, 4Ps in 12 dimensions, demographic of consumer and consumer behavior characteristics were shaped research framework. The main tool used in this study was questionnaires and the information about literature and history has been collected through libraries. The relationship among variables has been studied through correlation test. This study found that, place factor had the most important role for working women when they purchased their working clothes; consumer demographic factor and consumer behavior characteristic factor were correlated with consumer decision-making factor.